Dosimetric comparison and time consuming evaluations for neoadjuvant 5-fields versus 7-fields Intensity-Modulated Radiation Therapy for locally advanced rectal cancer. - Reali, Alessia (JOURNAL OF ADVANCES IN PHYSICS, 2015)
Aims and background: Preoperative multidrug - chemoradiotherapy schedule (PCR) is proven to be the standard approach in patients with locally advanced rectal cancer (LARC). The main limiting factor of PCR delivery is severe acute gastrointestinal (GI) toxicity due to the small bowel irradiated volume. Compared to 3-dimensional conformal radiation therapy (3DCRT), intensity-modulated radiotherapy (IMRT) plans, with 7 or more fields, by highly conformal dose distributions, will minimize the dose received by small bowel, but required an increase in overall treatment time. The purpose of this study was to investigate if simple IMRT plans were comparable to conventional 7-fields IMRT in terms of dose distribution, with the advantage of reducing time delivery.Twelve patients with histologically proved LARC underwent PCR with concurrent chemotherapy with Oxaliplatin 50 mg/m2 intravenously weekly x 6 weeks + Capecitabine 1500 mg/mq day (on days 1,14 every 21 days) and 7-field IMRT step-and -shoot technique at the cumulative dose of 50.4 Gy to the target volume, with conventional fractionation schedule of 1.8 Gy each day. Dose calculation for selected Organ at Risks (OARs) such as femoral heads, bladder and small bowel, were performed. Without exceeding OARs dose constraints or compromising target coverage, for each treated patients, a simpleIMRT plan with 5 fields was computed and retrospectively compared with 7-field IMRT. Dosimetric parameters and treatment time data were analized. As expected, homogeneity of dose distribution was significantly better for 7F-IMRT than 5F-IMRT; while in terms of Conformation Number, as proposed by vant Riet et. Al, we registered no statistically significant differences between the two IMRT techniques resulting in equal sparing of healthy tissues. We recorded a median delivering treatment time of 7.9 minutes for 5F-IMRT and of 12.3 minutes for 7F-IMRT, with a difference statistically significant. This preliminary study demonstrated that the reduction in the number of fields obtained with the 5F-IMRT is a strategy to improve treatment time delivery without a detriment in target coverage and normal tissue sparing in PCR for LARC patients.